A Study on Business Management of the Small Scale Sector In India: Impact of Government Measures and Multinational Entry on Small Scale Sector in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The recent industrial policy measures in regard to theSmall Scale Sector, adopted by the Government, have given the necessary jolt toget rid of the inertia developed by the sector. Various reasons like Governmentrestrictions on capital employed and the products manufactured, lack ofadequate growth opportunities and the absence of entrepreneurialprofessionalism may be identified as the major causes for this inactivity. The recent liberalization measures including therelaxation in the Monopolies and Restrictive Trade Practices Act and ForeignExchange Regulation Act along with reduction in import and excise duties haveprovided the required impetus through intensified competition by attracting themultinational organizations and other internationally established companies.This entry of multinationals into Indian markets will have to have its impacton all levels of indigenous manufacturing activity, be it in small, medium orlarge sector. Its impact on the Indian consumer is more intensive, for theinternationally renowned brands are made available in the local markets ataffordable prices. The impact of the entry of the multinationals on the mediumand large scale units is relatively lessened by the relaxation of the growthhurdles like Monopolies and Restrictive Trade Practices Act and ForeignExchange Regulation Act and other restrictions on foreign collaborativearrangements.